Упрости выражение:
(−5am^3n^2)^3÷(5mn)^2.

ответ: a m n

Aryyke08 Aryyke08    2   03.01.2022 18:30    0

Ответы
oksana1410 oksana1410  15.02.2022 15:12

- 5a^{3} {m}^{7} {n}^{4}

Объяснение:

( - 5am^{3} {n}^{2})^{3} \div (5mn) ^{2} = \frac{( - 5a {m}^{3} {n}^{2}) ^{3} }{(5mn)^{2} } = \frac{ - 125 {a}^{3} {m}^{3 \times 3} {n}^{2 \times 3} }{25 {m}^{2} {n}^{2} } = \frac{ - 125a^{3} {m}^{9} {n}^{6} }{25 {m}^{2} {n}^{2} } = - 5a^{3} {m}^{9 - 2}n^{6 - 2} = - 5a^{3} {m}^{7} {n}^{4}

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра